Respuesta :

Answer:

a) The solution of the given system is (x,y) = (-4,1)

b) The solution of the given system is (-6,-4)

Step-by-step explanation:

a) Step 1:-

The given equations are [tex]5 x-y = -21[/tex]........(1)

    given second equation is [tex]x+y = -3[/tex]......(2)

adding the equations (1) and (2) and cancelled y terms,we get

[tex]5 x+x=-21-3[/tex]

[tex]6x=-24[/tex]

dividing by '6' on both sides,we get

[tex]x=-4[/tex]

Step 2:-

substituting x =-4 in equation (1) and simplification , we get

[tex]5(-4)-y=-21[/tex]

[tex]y=1[/tex]

The solution of the system is (-4,1)

b) Explanation:-

Step 3:-

The given equations are [tex]\frac{5x}{3} -2 y=-2[/tex].........(3)

and second equation is [tex]-x+y=2[/tex]........(4)

solving the equations (3) and (4)

multiply equation  (4)  with '2'

[tex]-2 x+2 y =4[/tex] .......................(5)

now adding (3) and (5) equations and simplification , we get

[tex]\frac{5x}{3} -2 x=2[/tex]

taking l.c.m we get [tex]\frac{5 x-6 x}{3} =2[/tex]

[tex]\frac{-x}{3} =2[/tex]

[tex]x=-6[/tex]

Step 4:-

substituting x= -6 in equation (3), we get solution

[tex]\frac{5(-6)}{3} -2 y =-2[/tex]

now simplification we get [tex]y = -4[/tex]

The solution of the given system is (-6,-4)

Answer:-6,-4

so the answer is -6-4